2022
DOI: 10.1177/08862605221097444
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Non-partner Violence in Informal Settlements in Nairobi, Kenya

Abstract: Violence against women is a serious public health and human rights concern and can take many forms. Intimate partner violence (IPV) is the subject of the majority of research focused on violence against women around the world; yet the health consequences of non-partner violence (NPV) can be just as serious. There is a critical gap in literature focused on NPV and the co-occurrence of NPV and IPV in sub-Saharan Africa, particularly in informal settlements. The unique historical, political, social, geo-spatial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Women in informal settlements face several political, economic, social, environmental, and climatic factors that may contribute to stress and, in turn, impact sleep quality. Studies have shown that rates of interpersonal violence and common mental health issues are much higher for women in informal settlements in Kenya than in other populations in the nation (28, [40][41][42]. Research also suggests that women in informal settlements have the worst health outcomes of any population in Kenya (43).…”
Section: Discussionmentioning
confidence: 99%
“…Women in informal settlements face several political, economic, social, environmental, and climatic factors that may contribute to stress and, in turn, impact sleep quality. Studies have shown that rates of interpersonal violence and common mental health issues are much higher for women in informal settlements in Kenya than in other populations in the nation (28, [40][41][42]. Research also suggests that women in informal settlements have the worst health outcomes of any population in Kenya (43).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines IPV as any behavior within an intimate relationship, within the context of marriage, cohabitation or any formal or informal union [3], that leads to physical, mental, or sexual injury to others in the relationship, including physical harassment, sexual coercion, psychological torture, and controlling behaviors (WHO, 2002). IPV is a global public health issue and a violation of the rights of victims [4]. In 2018, the global estimates of lifetime prevalence of physical and or sexual IPV among women 15-49 years who have ever been married or partnered was highest in least developed countries at 37%, while Southern Asia and sub-Saharan Africa recorded 35% and 33% respectively [3,5].…”
Section: Introductionmentioning
confidence: 99%